Bridging the Digital-Language Gap: School Education in Rural and Urban Assam - Sarma, Himangshu Sekhar; Sarma, Indrani (Indian Journal of Educational Technology, 2025)
The proliferation of Information and Communication Technology (ICT) has given prominence to the digital divide discourse, which has become a subject of global concern. The multifaceted issue of digital divide and inequality is ingrained in broader cultural and socio-economic systems. These frameworks interact to create various opportunities and obstacles for various students in terms of access, understanding and effective use of digital technology for learning. Against this backdrop, this study also examines the relationship between linguistic proficiency as a form of cultural capital and digital divide in technology adoption among students in vernacular medium schools in Jorhat district of Assam. It finds that proficiency in dominant languages used in digital educational content and technological interfaces significantly enhances students’ access and agency over technology and broader digital communities within their respective actor-networks which not only results in better academic performance but also helps in accumulation of further cultural capital. Conversely, lack of proficiency in these languages among rural and tribal students hinders their ability to engage with technology for educational purposes. Further, lack of cultural capital among teachers and parents represents critical gaps in the actor-networks which hinder technology adoption among rural and tribal students.